Management guru and philosopher - Abd Razak, Dzulkifli (2006)
The year 2005 saw the world made a lot poorer by the death of many personalities: a pope, a literary figure, an inventor, a footballer and our very own traditional and heritage art lover. Not to mention the many talented people swept away by wars and violence, tsunami, hurricanes, earthquakes and, most recently, the floods at home and abroad. Let us also remember Peter Drucker, who died of natural causes, eight days before his 96th birthday. Born on Nov 19, 1909 in Austria, Drucker was known for a number of managementrelated concepts, namely management by objective (MBO), privatisation, decentralisation and outsourcing, among others.